Study on the Unsteady Pressure Fluctuations and Radial Forces in a Vaned-Diffuser Heavy-Liquid-Metal Centrifugal Pump - Xudan Ma; Hui Sheng; Chenyang Wang; Yao Lu; Kefeng Lyu (Energies)
Lead–Bismuth Eutectic (LBE) is a very dense medium whose specific gravity is more than 10 times that of water. The unsteady hydraulic exciting force generated by the rotor–stator interaction (RSI) is significantly increased in the LBE pump, which has an important influence on the stable operation of the pump. The clearance between the vaned diffuser inlet and the impeller outlet has great influence on the rotor–stator interaction. This paper studies the unsteady flow characteristics in pumps with different rotor–stator clearance in different flow rates and transported mediums. The results show that at the design point, the head and efficiency of the pump when transporting LBE are 3.52% and 8.05% higher than those when transporting water. The pressure fluctuation distribution is similar at different positions inside the pump when transporting LBE and water, but the dimensionless pressure fluctuation coefficient is slightly larger when transporting water. The radial force in the pump shows a larger amplitude of 6BPF frequency with small clearance ratios, and the frequency is related to the guide vane number. When the clearance ratio increases from 1.03 to 1.13, the amplitude of 6BPF keeps decreasing. The amplitude at a clearance ratio of 1.13 decreased to 4.7% of that at 1.03. The research presented in this paper could provide some references for the design of the clearance between the rotor–stator parts in the LBE pump.